Systematics of hairy armadillos and the taxonomic status of the Andean hairy armadillo (Chaetophractus nationi) - Abba, Agustín Manuel (2015)
Fil: Abba, Agustín Manuel. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología Vertebrados; Argentina